Analysis and Design of A Website-Based Batam Local Courier Information System - Muhammad Ikhlash; Irsutami Irsutami; Sugeng Riadi; Fathia Mayang Sari (Pusat P2M Politeknik Negeri Batam, 2023)
The impact of the Minister of Finance Regulation (PMK) Number 199 concerning Customs, Excise, and Tax Provisions on the Import of Consignments in 2019 which was enacted since January 30, 2020 is a decrease in online sales in Batam. As a result, MSMEs in Batam City have to change their market share to only focus on the people of Batam as a strategy in maintaining their business. Based on the results of interviews with several people selling goods whose consumers are in Batam City, they basically prefer local couriers. However, there are some problems, namely the position of goods cannot be tracked in real-time as is the case with e-commerce applications. Where local courier companies have not been integrated with information system applications. The purpose of this study was to analyze the local courier information system of Batam City and to design the local courier information system of Batam City. The first method used is to collect and data through observation, interviews, and literature studies. Then design an information system by analyzing the running system, analyzing system needs, and designing a website interface that combines 3 points of view, namely local courier companies, sellers and consumers. The conclusion of this study is that this research has produced a draft information system for shipping goods for local couriers in Batam City. The information system developed has used data integration through the delivery database of goods available in data management. This information system can help customers to carry out the process of tracking goods that so far cannot be done if using a local courier in Batam City.